Feasibility of realizing daytime solar heating and radiative cooling simultaneously with a novel structure. (November 2021) - Hu, Mingke; Zhao, Bin; Suhendri,; Cao, Jingyu; Wang, Qiliang; Riffat, Saffa; Su, Yuehong; Pei, Gang
Highlights: A new idea of realizing solar heating (SH) and radiative cooling (RC) simultaneously. The radiative emitter temperature is sensitive to the solar absorber temperature. Vacuum helps to relieve the emitter from heating up by the absorber. The emitter can reach a sub-ambient temperature reduction of over 9.3 °C around noon. Abstract: Recent breakthroughs in preparing near-perfect emitters have made it possible to realize daytime radiative cooling under intensive solar radiation. However, a typical radiative cooler cannot deliver heat and may even cause an undesired cooling effect on cold days. Instead of rejecting the solar radiation back to the sky, this work proposes a new concept of capturing this "free" renewable energy while dumping waste heat through radiative cooling. The new structure features an upper solar-transparent radiative emitter and a lower solar absorber. Simulation results suggest that, to realize daytime solar heating and radiative cooling simultaneously, the emitter solar-absorptivity should be extremely low, and the absorbed solar heat should be instantly and effectively taken away by thermal carriers. With an ambient temperature of 25 °C and a maximum solar irradiance of 1000 W/m 2, the emitter can always reach a sub-ambient temperature if the absorber temperature is lower than 33.9 °C in the non-vacuum case, and can exceed 70 °C if the air cavity between the emitter and absorber is vacuumized. A performance simulation in three consecutive days in Shanghai reveals that the emitter can realize daytime radiative cooling with a temperature reduction of over 9.3°C from the ambient temperature around noon.